A simple method for determining the lattice parameter and chemical composition in ternary bcc-Fe rich nanocrystals - Moya, Javier Alberto (2015)
Charts containing lattice parameters of Fe1-x(M,N)x ternary systems with M and N = Si, Al, Ge or Co, and 0 ≤ x ≥ ∼0.3, were developed by implementing a linear relationship between the respective binary alloys with the same solute content of the ternary one. Charts were validated with experimental data obtained from literature. For the Fe-Co-Si system, the linear relationship does not fit the experimental data. For the other systems (except the Fe-Co-Ge one where no experimental data was found), the lineal relationship constitute a very good approximation. Using these charts and the lattice parameter data obtained from X-ray diffraction technique combining with the solute content data obtained from Mössbauer spectroscopy technique it is possible to determine the chemical composition of nanograins in soft magnetic nanocomposite materials and some examples are provided.